2010
DOI: 10.1002/jmri.22298
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of FAIR imaging for evaluating tumor perfusion

Abstract: Purpose: To evaluate the feasibility of flow-sensitive alternating inversion recovery (FAIR) for measuring blood flow in tumor models. Materials and Methods:In eight mice tumor models, FAIR and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) was performed. The reliability for measuring blood flow on FAIR was evaluated using the coefficient of variation of blood flow on psoas muscle. Three regions of interest (ROIs) were drawn in the peripheral, intermediate, and central portions within each tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…In our study, the mean HBFI was approximately 8 times higher and blood flow in HCC was approximately 10 times higher than the blood flow of the erector spinae muscle, which is consistent to a recent study comparing tumor perfusion to perfusion of the psoas muscle in an animal model (32). Moreover, we observed slight differences in the intrahepatic blood flow between left and right liver lobes as well as a higher mean SBFI compared with the mean HBFI, which is also consistent with recent literature (33, 34).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the mean HBFI was approximately 8 times higher and blood flow in HCC was approximately 10 times higher than the blood flow of the erector spinae muscle, which is consistent to a recent study comparing tumor perfusion to perfusion of the psoas muscle in an animal model (32). Moreover, we observed slight differences in the intrahepatic blood flow between left and right liver lobes as well as a higher mean SBFI compared with the mean HBFI, which is also consistent with recent literature (33, 34).…”
Section: Discussionsupporting
confidence: 92%
“…Besides artifacts caused by movement, susceptibility difference, magnetic field inhomogeneity and fat near the abdomen, the sensitivity of ASL to low perfusion in tumor makes imaging especially difficult. A study compared ASL and DCE‐MRI in mouse tumor and found high correlation between blood flow and K ep , the rate constant of transfer between the extracellular space and the blood plasma . However, large variability and very high flow (207 ± 111 mL/100 g/min) values were reported in center of tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter obtained with curve-pattern analysis has a strong correlation with k ep . 16 Because k ep has been shown to be sensitive to treatment in previous literature, 17,18 this finding suggests a similar role for .…”
Section: Discussionmentioning
confidence: 56%